KEBIJAKAN PERLINDUNGAN ANAK BINAAN LEMBAGA PEMASYARAKATAN DI MASA PANDEMI COVID-19 - Rini Fathonah; Niko Alexander; Nikmah Rosidah; Mashuril Anwar (UNES Journal of Swara Justisia, 2021)
Based on humanitarian considerations and human rights enforcement, the Indonesian government through the Ministry of Law and Human Rights of the Republic of Indonesia has issued a policy to protect children in prisons during the Covid-19 pandemic. This policy is not far from the pros and cons of various circles. On the one hand, the policy is welcomed to reduce the spread of Covid-19, on the other hand, the policy is considered to disturb public security. Therefore, the policies of the Ministry of Law and Human Rights, especially those related to child protection during the Covid-19 pandemic, are important to be further reviewed in this article. This research is normative legal research / doctrinal research. The approach used in this research is the statutory approach (statute approach), analytical approach (analytical approach), conceptual approach (conceptual approach), and the case approach (case approach). The increasingly massive spread of Covid-19 poses its challenges in protecting children as a vulnerable group. Responding to this condition, the central government issued several policies to protect children during a pandemic. These policies include Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 10 of 2020 concerning Terms of Providing Assimilation and Integration Rights for Prisoners and Children in the Context of Preventing and Combating the Spread of Covid-19, as well as Decree of the Ministry of Law and Human Rights Number M.HH-19. .PK / 01.04.04 concerning the Release and Release of Prisoners and Children through Assimilation and Integration in the Context of Preventing and Combating the Spread of Covid-19. Keywords: Covid-19, Child Protection, Policy